2011
DOI: 10.1016/j.jmii.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Isolated pathogens and clinical outcomes of adult bacteremia in the emergency department: A retrospective study in a tertiary Referral Center

Abstract: Categories of bacteremia acquisition was associated with different distribution of pathogens, antimicrobial resistance, and clinical outcome. Traditional classification might overestimate the problem of drug resistance in community-acquired infections. The concept of health care-associated infection should be introduced to avoid overemphasis of drug-resistant problem in true community-acquired infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
4
25
4
Order By: Relevance
“…The receipt of intravenous therapy [7,14,30,31,35-39,41,45-47], wound care or specialized nursing care [34-37,41,42,45], and hemodialysis [7,11-14,31-42,44-46], as well as attendance at a hospital or clinic [32,42,44,45] are important factors as this group of patients has documented higher rates of colonization and infection with MDR microorganisms [48-50]. Three additional studies have included the criteria of other previous invasive procedures [7,30,45], like urological procedures [45]. There is no reason to believe that this last group of patients is different from the previous ones in regards to the risks of infection by MDR organisms, so we propose that the first criterion be generalized to include all patients that received invasive procedures in the 30 days before the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The receipt of intravenous therapy [7,14,30,31,35-39,41,45-47], wound care or specialized nursing care [34-37,41,42,45], and hemodialysis [7,11-14,31-42,44-46], as well as attendance at a hospital or clinic [32,42,44,45] are important factors as this group of patients has documented higher rates of colonization and infection with MDR microorganisms [48-50]. Three additional studies have included the criteria of other previous invasive procedures [7,30,45], like urological procedures [45]. There is no reason to believe that this last group of patients is different from the previous ones in regards to the risks of infection by MDR organisms, so we propose that the first criterion be generalized to include all patients that received invasive procedures in the 30 days before the infection.…”
Section: Discussionmentioning
confidence: 99%
“…This is a criterion frequently used among alternative definitions [7,14,30,31,35,38-40,42,44],[45] along with having active or metastatic cancer [11,32] that suggest receipt of some kind of anti-cancer therapy. These are a special group of patients due to underlying immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…All hospitals are requested to reduce cost; therefore, newer antimicrobial agents those may cost more are restricted from being used as the initial antibiotics in some hospitals. Even though most antimicrobial resistance surveillance studies show that the major pathogens in Taiwan are resistant to the first or secondary generations of beta-lactams and aminoglycosides [20,23,24], cefazolin, gentamicin and amoxicillin/clavulanate are still common choices of empiric antibiotics in community hospitals. Our result alerts clinicians to notice impact on patient outcomes due to inappropriate antibiotic administration.…”
Section: Discussionmentioning
confidence: 99%
“…The infectious diseases society of American previously stated that an antibiotic may reasonably remain an appropriate empirical agent if less than 20% of the likely pathogens show in vitro resistance. 11, 13 In our study, cefazolin had more than 80% effectiveness against E. coli, K. pneumoniae , and P. mirabilis , and these three organisms comprised 80% of detected uropathogens.. A separate study conducted in southern Taiwan also showed low rate of resistance to cefazolin and still supported cefazolin as appropriate empirical antibiotic for UTI [10]. Importantly, we were able to determine when cefazolin would likely fail; cefazolin should be avoided in male patients with a urinary catheter or nephrolithiasis and in female patients with diabetes and malignancy.…”
Section: Discussionmentioning
confidence: 51%
“…This observation suggests that UTIs are the commonest etiology of community-acquired bacteremia [10]. Appropriate treatment of bacteremia during sepsis could further reduce case-mortality.…”
Section: Discussionmentioning
confidence: 99%